Effects of Dose Amount for Antiepileptic Drugs on Lipid Profile of Male Rats (Rattus Norvegicus). - Mohsin Abbas, Abbas (University of Thi-Qar Journal of Science, 2017)
The present study aimd to estimate the changes in lipid profile depend on dosage amount of two AEDs ,Phenytoin (PHT) and Carbamazepine (CBZ) , and make a comparison between them in rats. A 30 healthy male Wistar rats (150-200 g) ( subdivide to five groups ) first group was control , the second and third groups received (50 mgand 100 mg) of Phenytoin respectively, fourth and fifth groups received (25 mg/kg and 50 mg/kg) of Carbamazepine respectively. Serum total cholesterol (TC), triglycerides (TGs) and High-density lipoprotein (HDL) levels were measured after 20 days period of treating, Low-density lipoprotein (LDL) and Very low-density lipoprotein (VLDL) was calculated also. Our data revealed that, the administration of PHT (50 mg) and CBZ (25 mg) didn’t affect serum lipid profile significantly compared to control group in male rats except the levels of VLDL in CBZ (25 mg) group which increased significantly (p-value <0.05) compared to control group, on the other hand we found that the administration of double dose (PHT 100 mgand CBZ 50 mg/kg) in group3 and group5 respectively caused a significant increase in TC, TGs, LDL and VLVL in both groups compare to control group. According to our results we conclude that the doubling the dose of CBZ and PHT cause an increase in cholesterol, TGs, LDL and VLDL and switching from CBZ and PHT to another drugs or decrease the dosage could contributes to avoid effects on the lipid metabolism profile of patients with chronic epilepsy